Valuation of risky assets in arbitrage-free economies with transactions costs - Garman, Mark B.; Ohlson, James A. (Journal of Financial Economics, 1981)
This paper analyzes the equilibrium valuation of risky assets in the case where transactions costs are present. The methodology involves applying ‘theorems of the alternative’ (Farkas' Lemma) as a consequence of arbitrage-free markets. Under relevant assumptions, it is found that the price of an asset having transactions costs is the corresponding price that would obtain in a perfect market, plus a ‘fudge factor’. This latter factor is provided explicit bounds.